Collaboration Tripartite Elements Accident Reporting and Potential Hazards Management Coal Mining, Indonesia: Systematic Review - Sultan, Muhammad (Journal of Health Science and Medical Research (JHSMR), 2023)
Objective: Occupational accidents and diseases in Indonesia are still a scourge because they not only cause minor and serious accidents, but often result in fatalities. The same occupational accidents and diseases’ would seem to be happening in the coal mining business sector. According to the Badan Penyelenggara Jaminan Sosial Indonesia, 234,370 cases of work accidents and work-related illnesses occurred in 2021, of which the mining sector contributed 6,565 cases. Collaboration between companies, workers and local governments in the management of work accident reporting needs special attention so that similar incidents do not occur in the future.Material and Methods: This literature review supports the researchers hypothesis or belief in disclosing that there is an increasingly open space for collaboration between companies, workers and local governments in accident reporting management to reduce accidents. The literature review search term used is work accident reporting sourced from Google Scholar, National Library of Indonesia, PubMed, and other sources in the 2017-2022 period.Results:This literature review found a number of facts that companies have an obligation as stipulated in the Regulation of the Minister of Manpower of the Republic of Indonesia No. 03 of 1998 concerning Accident Reporting and Investigation Procedures to report every work accident and work-related illness that occurs both periodically and specifically to the competent authority. Likewise, workers have the responsibility to report any accidents and potential hazards found in the workplace to the occupational safety and health officer. The Regional Government is no exception, which is a regulator and at the same time supervises companies in carrying out their business activities.Conclusion: To reduce workplace accidents requires diligent and constructive cooperation between the business managers, the workers, and the government regulators to support a zero-accident work environment.